39 Ma U-Pb zircon age for the Shaki-Rash gabbro in the Bulfat igneous complex, Kurdistan region, Iraqi Zagros Suture zone: rifting of an Intra-Neotethys Cenozoic arc - Ali, Sarmad Asi (Ofioliti, 2017)
The suprasubduction Bulfat Igneous Complex in NE Iraq is one of the discontinuous Neotethys oceanic lithosphere fragments preserved in the Zagros region. Reported here are new geochronological, petrological and geochemical data from this assemblage. At the study locality, Eocene arc-related magmatic rocks are intruded by extensive dykes of Shaki-Rash gabbro. The key reason to focus on these rocks is the remarkable lack of hydrothermal alteration, including preservation of very fresh olivine. Besides olivine the gabbros contain plagioclase and clinopyroxene, with lesser orthopyroxene, biotite, brown hornblende and alkali feldspar. From mineral chemistry, the crystallization conditions of the olivine gabbros are 950-1050°C and 5-3 Kbar. Shaki-Rash gabbro shows alkaline affinity. SHRIMP U-Pb dating of magmatic zircon from the gabbro yielded a mean 206Pb/238U age of 39.0±0.5 Ma (Eocene). Most of the Shaki-Rash gabbro samples have Ti/V of 100 to 50 and fall in the back-arc basin (BAB) and alkaline fields, while on a Nb/Yb-Th/Yb diagram, most samples fall within the MORB-OIB array and plot in proximity to E-MORB. Primitive-mantle-normalized trace-element patterns show enrichment in the large ion lithophile elements without depletion of the high-field-strength elements. These geochemical signatures and their field setting advocate for the formation of these dikes in an extensional tectonic environment, such as an intra-arc rift.